PENINGKATAN KETERAMPILAN MOTORIK HALUS MELALUI METODE DEMONSTRASI DENGAN KOLASE PADA ANAK KELOMPOK B TK PERTIWI II BANGKLE BLORA TAHUN AJARAN 2015/2016 - Kiswati, Kiswati, Drs. Suyatmin Waskito Adi, M.Si (2015)
The aims of this research are (1) The Improvement of the Fine Motoric Skills thourgh the Demonstration Method with Collage on the Children (2) to increase the teachers ability enhancing the children's fine motoric ability (3) to apply the demonstration method with collage in improving the fine motoric ability of the children of the Group B Pertiwi II Bangkle Blora Kindergarten. This research uses the class-room action research type which consists of planning action. Observation and reflection by applying the collage activities which are connducted in two cycles. The research is measured from the observation dan documentation results at every cycle. From the observation it is noticed that the improvement of the fine motoric ability of the observation it is noticed that the improvement of the fine motoric ability of the children occurs. The enthusiasm of the children in the collage activities before the research was 7 children (35%), Cycle I consists of 14 children (70%), Cycle II consists of 16 children (80%). Based on the finding it cold be conclued that the collage activities could improve the fine motoric ability on the children of the Group B of Pertiwi II Bangkle Blora Kindergarten.